Investment in the Absence of Property Rights: The Role of Incumbency Advantages - Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2002)
In many situations the individuals who can generate some output must enter a contest for appropriating this output. This paper analyses the investment incentives of such agents and the role of incumbency advantages in the contest. Depending on the advantages, an increase in the productivity of the investment can decrease or increase the amount of investment. The results are applied to autocrats' investment behavior and job specific investment in organizations.
Keywords: 330; investment; endogenous property rights; contests; incumbency advantage; proprietary states